2007
DOI: 10.1002/bmc.952
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of domperidone in human plasma by ultraperformance liquid chromatography with electrospray ionization tandem mass spectrometry

Abstract: A simple and sensitive liquid chromatography-tandem mass spectrometry method was developed and validated for determining domperidone in human plasma. The analyte and internal standard (IS; mosapride) were isolated from plasma samples by protein precipitation with methanol (containing 0.1% formic acid). The chromatographic separation was performed on an Xterra MS C(18) Column (2.1 x 150 mm, 5.0 microm) with a gradient programme mobile phase consisting of 0.1% formic acid and acetonitrile at a flow rate of 0.30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
0
16
0
2
Order By: Relevance
“…Kobilińska et al previously reported an HPLC method using solid-phase extraction (SPE), which required a post-column photoderivatization for fluorescence detection [9]. Recently, Xu et al proposed an LC-MS/MS method with direct injection after simple protein precipitation [7]. LC-MS/MS method could be the best choice in terms of sensitivity and specificity, but this equipment is not always available in many laboratories.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kobilińska et al previously reported an HPLC method using solid-phase extraction (SPE), which required a post-column photoderivatization for fluorescence detection [9]. Recently, Xu et al proposed an LC-MS/MS method with direct injection after simple protein precipitation [7]. LC-MS/MS method could be the best choice in terms of sensitivity and specificity, but this equipment is not always available in many laboratories.…”
Section: Introductionmentioning
confidence: 97%
“…Several HPLC methods have been reported for the determination of domperidone in plasma [6][7][8][9][10][11][12]. Most of these methods required time-consuming laborious liquid-liquid Page 4 of 30 A c c e p t e d M a n u s c r i p t -3 -extraction procedures [6,8,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…These methods lack of sensitivity and require extensive sample preparation before analysis. Mass spectrometry has played an important role in toxicology due to its sensitivity, rapidity and low levels of sample consumption for the characterization and determination of many toxic compounds (Cao et al, 2008;Chou et al, 2008;Jin and Chen, 2006;Jin et al, 2007;Li et al, 2008;Xiao et al, 2008;Xu et al, 2008;Yao et al, 2006). Recently, Shao et al (Shao et al, 2006) developed an analytical assay to detect triptolide in dog plasma samples by high-performance liquid chromatography coupled with atmosphericpressure-chemical ionization mass spectrometry (HPLC-APCI-MS).…”
Section: Introductionmentioning
confidence: 97%
“…Compared with HPLC, ultra-performance liquid chromatography (UPLC) is a relatively new technique using analytical Bridged Ethane Hybrid (BEH) C 18 columns packed with 1.7 μm particles, mobile phases at high linear velocities, and instrumentation that operates at high pressure. UPLC, therefore, offers the advantages of increased speed during analysis, higher sensitivity and greater resolution for analytical determination, particularly when coupled with mass spectrometry (O'Conner and Mortishire-Smith, 2006;Li et al, 2007;Mensch et al, 2007;Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 98%